Looking after Louis - Ely, Lesley; Dunbar, Polly (Morton Grove, IL : Albert Whitman, 2004)
When a new boy with autism joins their classroom, the children try to understand his world and to include him in theirs.
Keywords: Autism -- Fiction; Schools -- Fiction